Two dimensional computational analysis of flow induced vibrations - Mutlu, Asım Ozan (My University, 2019)
One of the difficult challenges that engineers encounter nowadays is the Vortex Induced Vibration (VIV). VIV occurs when a bluff body is subjected to external fluid flow. Vortices shed from the structures cause bluff bodies to oscillate. This oscillation can lead to failures of the structures. With the recent development of computer technologies, VIV have been caught attention by many researchers. Although, extensive research has been done until now, there are still research areas to be investigated on VIV. In this study, one of the most important parameters of VIV, which is damping of the structure, is investigated and the results are compared with the experimental study of the previous research. The simulations are done with 2D cylindrical cross-section structure that is free to move in transverse direction. Overall, the general trend is well captured, however due to 2D limitations some results are not consistent with experimental data. The results are shown and overall, it is concluded that the response of the amplitude decreases with the increased damping of the structure and a shift occurs in the beginning of the lock-in region with increasing damping.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2019
Keywords: Computational fluid dynamics; Cortex-Induced vibration; URANS method; Damping